Aisas Marketing Model In Promoting Repaint Services Through Tiktok Social Media (A Study On Tiktok Account @As_Carbon) - Putra, Rama Anandra; Narti, Sri; Dianthi, Martha Heriniazwi (Journal of Multidisciplinary Research, 2025)
This study analyzes the content strategy of the TikTok account as_carbon in promoting repaint services based on the AISAS model stages (Attention, Interest, Search, Action, Share). TikTok was chosen due to its ability to spread short, engaging, and potentially viral content organically. Using a qualitative descriptive approach, data was collected through content observation, interviews with the account owner, admin, and active customers, as well as documentation of audience interactions. The results show that as_carbon consistently implements each stage of AISAS. In the Attention stage, the account uses before-after videos with engaging visuals and trending music. Interest is built through educational and informative content about the service process and its advantages. In the Search stage, the audience seeks additional information via WhatsApp and Instagram links in the bio. The Action stage is shown by increased service orders through DM and direct communication. Lastly, the Share stage is evident through customer testimonials and voluntary sharing on social media. The study concludes that the AISAS-based content strategy effectively enhances visibility, builds trust, and drives conversion and audience participation. TikTok proves to be a powerful promotional tool for service-based businesses like repaint.